Biosimilars: a position paper of the European Society for Medical Oncology, with particular reference to oncology prescribers - Tabernero, Josep (ESMO Open, 2017)
Biosimilars present a necessary and timely opportunity for physicians, patients and healthcare systems. If suitably developed clinically, manufactured to the correct standards and used appropriately, they can positively impact on the financial sustainability of healthcare systems. A critical consideration regarding the introduction of biosimilars into the clinic centres on the required information concerning all the respective procedures. This position paper aims to describe the issues revolving around biosimilars that are relevant to the field of oncology, especially the prescribers. More specifically, we discuss aspects related to definition, forms of biosimilars, labelling, extrapolation, interchangeability, switching, automatic substitution, clinical standards on safety and efficacy, responsibilities among prescribers and pharmacists, potential impact on financial burden in healthcare and the current scenario and future prospects of biosimilars in Europe and the rest of the world.